Pengembangan Bahan Ajar Bahasa Indonesia untuk Pembelajaran Membaca di Sekolah Dasar - Warman, Enjang (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
This article will describe the development of teaching materials for elementary school children’s reading. The development of teaching materials is intended to improve students’ reading skills and understanding of historical texts that contain character values for students. The research was conducted in class VI of State Elementary School 1, Gekbrong District, Cianjur Regency, West Java Province. The type of research used is R&D/Research and Development. The development of these teaching materials is able to meet the needs of Indonesian language teaching materials at SDN Gekbrong 1. The content of the teaching materials explores information from historical narrative texts containing character values for class VI students that are in accordance with the needs of class VI students at SDN Gekbrong 1. Keywords: teaching materials; reading; character education; story text ABSTRAK Artikel ini akan mendeskripsikan pengembangan bahan ajar pembelajaran membaca anak SD. Pengembangan bahan ajar dimaksudkan untuk meningkatkan kemampuan membaca dan pemahaman peserta didik terhadap teks sejarah yang bermuatan nilai-nilai karakter bagi siswa. Penelitian dilakukaan di kelas VI Sekolah Dasar Negeri 1 Kecamatan Gekbrong Kabupaten Cianjur Provinsi Jawa Barat. Jenis penelitian yang digunakan adalah R&D/Research and Development. Pengembangan bahan ajar ini mampu memenuhi kebutuhan bahan ajar Bahasa Indonesia di SDN Gekbrong 1. Isi materi bahan ajar menggali informasi dari teks narasi sejarah bermuatan nilai-nilai karakter pada peserta didik kelas VI yang sesuai dengan kebutuhan peserta didik kelas VI SDN Gekbrong 1. Kata kunci: bahan ajar; membaca; pendidikan karakter; teks cerita